Pengaruh Corporate Social Responsibility Terhadap Earning Quality Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 - 2017 - Supriani Hutasoit; Khairunnisa Harahap; Akmal Huda Nasution (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2020)
Abstract : The problem in this research is that the number of companies conducting corporate social responsibility (CSR) at the moment to get a positive image of the parties concerned with the sustainability of the company. On the other hand, management can also perform actions such as earnings management practices. Therefore, this study aimed to examine whether the company contributes to corporate social responsibility (CSR) tend to avoid actions kualitias profit management resulting in better profit or otherwise. In this study aimed to examine the effect of disclosure of corporate social responsibility towards the quality of earnings in mining companies listed on the Indonesia Stock Exchange 2015-2017.The study population was a mining company listed on the Stock Exchange in  2015-2017  as  many  as  42  companies.  Samples  are  12  companies  with purposive  sampling  method,  with  quantitative research.  The  data  used  is secondary data, the company's financial statements were    obtained from www.idx.co.id, https://finance.yahoo.com,  as well  as  from  the  company's official  website.  The  data  analysis  technique used  is  descriptive  statistics, normality test, assuming classical, multiple regression analysis, the coefficient of determination, F-statistics test and t-test statistics.The dependent variable in this study is the quality of earnings through proxied using discretionary accruals (DAC). The independent variable used is CSR and CSR Index (CSRI) using GRI guidelines. This study also uses control variables firm size, leverage, and profitability. The analytical method used in this research is regression analysis with SPSS 20. Based on the results of this study to simultaneously show that CSR variables significantly influence the quality of earnings through discretionary accruals (DAC). This is evidenced by the significant value of CSR simultaneously (Test f) of 0.001 or less than 0.05. While the significance of CSR partially (t test) of0.489 or greater than 0.05. It is concluded that CSR simultaneously affect the earnings quality. However, CSR is partially no effect on earnings quality through discretionary accruals (DAC). While the control variables in this study such as firm size and leverage does not affect the quality of earnings. While the profitability variable effect on earnings quality. Keywords: Earnings Quality, Corporate Social Disclosure, Firm Size, Leverage and Profitability